Stress for aluminum in plants: reactions in the soil, symptoms in plants and amelioration possibilities. A review (2018)
In the most acid soils worldwide, covering up to 40% of the surface potentially usable for crops, aluminum is the most growth and yield limiting factor. It is estimated that about 85% of the total land surface in Colombia is composed by acid soils where the productivity of most food crops is severely restricted due to soil acidity and aluminum toxicity. In acid mineral soils with pH values below 5,5 a large proportion of the cation exchange sites of clay minerals is occupied by aluminum where it specially replaces other polyvalent cations as Mg2+ and Ca2+ and simultaneously acts as a strong absorber of phosphate. The strong competing effect of aluminum on calcium and magnesium uptake explains why the molar ratios of Ca/Al, Mg/Al or (Ca+Mg+K)/Al in the soil or nutrient solutions are sometimes better parameters for predicting of the risk of aluminum-induced bases deficiency than the concentrations of any individual elements. The initial effect of aluminum stress is the inhibition of root growth, moreover aluminum accumulation is an indicator of Al-sensitivity takes place in the root apex; Al-resistance mechanisms are confined mainly to the root apex; and callose formation is induced in apical cells of the roots. Some amelioration possibilities to aluminum stress are: application of organic matter to the soil, root colonization with mycorrhizas, application of organic acids to the nutrient solution, foliar application of phosphorus, and lime application to the soil, Al-tolerant plants selection, and transgenic tolerant plants.